Report of inquiry into safety in the long haul trucking industry - Quinlan, Michael (University of New South Wales, 2001)
"The report examined the impact of commercial practices, including the role of clients and the effects of elaborate subcontracting chain, on safety. The report draw on interviews with a wide range of parties, a survey of 300 long haul drivers and examination of reports, previous inquiries and other documentary information. Comparisons are also made with the situation in the European Union and North America. The report highlighted the safety risks posed by long hours of work and low payments to drivers. A series of recommendations made to address these issues are currently under consideration. "